Saving â€œSave In Accordance With Lawâ€: A Critique Of Kulasingam V. Commissioner Of Lands, Federal Territory - Yusof, Mohd Ariff (Journal of Malaysian and Comparative Law, 2019)
The phrase "save in accordance with law" occurs in two contexts in the Constitution of Malaysia: Article 5(1) ("No person shall be deprived of his life or personal liberty save in accordance with law") and Article 13(1) ("No person shall be deprived of property save in accordance with law"). In each the meaning ascribed to that phrase has in the past been generally narrow and positivistic. As far as Article 5(1) is concerned, the high-water mark is seen in Karam Singh v Menteri Hal Ehwal Dalam Negeri where "law" is articulated as to include substantive law but to exclude procedure.